Evaluación de la vegetación urbana y temperatura superficial terrestre en la reducción de islas de calor en la ciudad de Pichincha - Mendoza Vélez, José Miguel (2026)
The main objective of this research was to analyze the relationship between urban vegetation and land surface temperature in the Pichincha canton, with the purpose of identifying its influence on the generation of urban heat islands. To achieve this, three main approaches were developed: first, assessing vegetation coverage through the Normalized Difference Vegetation Index (NDVI) using Landsat 8 satellite images; second, calculating Land Surface Temperature (LST) by converting atmospheric radiance, brightness temperature, vegetation fraction, and surface emissivity; and third, determining the intensity of the urban heat island phenomenon based on the relationship between NDVI and LST. Subsequently, a statistical analysis was conducted to determine the degree of correlation between these variables. The results showed variations in vegetation coverage, with a maximum value in 2020 (0.5357) and a minimum in 2024 (0.0444). Regarding LST, the highest temperature was recorded in 2020 (32.40 °C) and the lowest in the same year (20.22 °C), confirming that areas with scarce vegetation present higher thermal levels. The correlation analysis revealed a significant inverse relationship between NDVI and LST (-0.76 to -0.82), supporting the role of vegetation in temperature regulation. Likewise, it was identified that densely urbanized areas, such as the center of Pichincha canton, presented greater heat island intensity, while areas with tree coverage recorded lower temperatures.